Teachers' Difficulties in the Implementation of the Pancasila Student Profile Strengthening Project (P5) at SMAN 5 Mataram - Siddiq, Muhammad Faqih; Mustari, Mohammad; Alqadri, Bagdawansyah; Zubair, Muh. (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The Pancasila Student Profile Strengthening Project (P5) is an integral part of the Independent Curriculum which aims to develop students' character and competencies holistically. However, the implementation of P5 in the field, especially at SMAN 5 Mataram, still faces various challenges. This study aims to identify and describe the difficulties faced by teachers in the implementation of P5 at SMAN 5 Mataram. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with teachers, observation of the implementation of P5, and documentation studies. The results of the study show several difficulties faced by teachers, including: (1) lack of teachers' understanding of the concept and objectives of P5; (2) limited time and resources in project planning and implementation; These findings have important implications for policymakers and schools to improve the effectiveness of P5 implementation through the provision of adequate training, mentoring, and resources for teachers.